Desain Kendali Stabilitas Konverter DC/AC pada Sistem PV Terhubung ke Grid - Huda, Zulmiftah (ELECTRON Jurnal Ilmiah Teknik Elektro, 2021)
PV systems has an important role in compliance of electrical demand. PV systems depends on sunlight intensity so that the PV output is nonlinear, this is a challenge in the control system design of PV system can maintain voltage and frequency stability. The P&O method based MPPT is applied to get the maximum power output of PV. The PWM control inputs are a reference Id from the MPPT and the voltage and current from the grid tied with Phase Looked Loop (PLL) for synchronization PV inverter. The control scheme given can provide stability voltage on the load against to the radiation changes that occur in PV